2016
DOI: 10.1002/jso.24136
|View full text |Cite
|
Sign up to set email alerts
|

Importance of surgical margins in rectal cancer

Abstract: Distal resection margin (DRM) and circumferential resection margin (CRM) are two important considerations in rectal cancer management. Although guidelines recommend a 2 cm DRM, studies have shown that a shorter DRM is adequate, especially in patients receiving neoadjuvant chemoradiation. Standardization of total mesorectal excision has greatly improved quality of CRM. Although more patients are undergoing sphincter-saving procedures, abdominoperineal resection is indicated for very distal tumors, and pelvic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 105 publications
1
37
0
1
Order By: Relevance
“…In fact, clinical experience and the literatures tell us that lower rectal cancer is more likely to appear a DRM <1 cm, or even a positive DRM, which is related to the surgical technique and difficulty. 5 Distant metastasis is associated with N stage, but not T stage, which is also in line with our expectations. Of course, regardless of T or N stage, after correcting multiple factors, this is corrected by the more superior TNM stage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In fact, clinical experience and the literatures tell us that lower rectal cancer is more likely to appear a DRM <1 cm, or even a positive DRM, which is related to the surgical technique and difficulty. 5 Distant metastasis is associated with N stage, but not T stage, which is also in line with our expectations. Of course, regardless of T or N stage, after correcting multiple factors, this is corrected by the more superior TNM stage.…”
Section: Discussionsupporting
confidence: 91%
“…The use of circular end-to-end staplers has revolutionized rectal surgery. 5 The use of this surgical instrument results in the resected specimen being divided into two parts. In addition to the main specimen, there is a "doughnut" with a resection margin of <5 mm.…”
mentioning
confidence: 99%
“…Most studies demonstrated no significant difference in local recurrence with distal rectal margins greater than or less than 1 cm, particularly in conjunction with neoadjuvant therapy [21]. In contrast, an inadequate circumferential margin (less than 1-2 mm) was associated with increased risk of local recurrence and a decreased disease-specific survival rate [21]. …”
Section: Rectal Adenocarcinoma Versus Rectal/pelvic Leiomyosarcomamentioning
confidence: 99%
“…The development of surgical techniques, stapling devices (staplers) and wide application of neoadjuvant chemotherapy and radiotherapy, this surgical procedure is increasingly giving way to previously described sphincter-preserving surgical procedures. However, it still serves as the method of choice for all patients diagnosed with T2-T4 rectal cancer where it is not possible to achieve tumor free distal margin of at least 1-2 cm, with locally advanced rectal cancer and low infiltration of the sphincter mechanism and / or rectovaginal septum, as well as those patients with poor preoperative function of the sphincter mechanism [15]. Abdominoperineal extirpation removes the rectum with tumor and anus (including total mesorectal excision and sphincter mechanism), and part of sigmoid colon, with the formation of a permanent terminal colostomy.…”
Section: Radical (Transabdominal) Operating Proceduresmentioning
confidence: 99%